The Relationship between Maternal Anemia and Retinopathy of Prematurity in Newborns - Vahid Aminzadeh; Reza Sharafi; Afagh Hassanzadeh Rad; Sadroddin Mahdipour (Iranian Journal of Neonatology, 2025)
Background: Retinopathy of Prematurity (ROP) is a leading cause of blindness in developed and developing countries. Maternal anemia can endanger the health of the fetus. Studies suggest a link between maternal anemia and an increased risk of ROP in newborns. Therefore, this study aimed to determine the relationship between maternal anemia and ROP in newborns. Methods: This cross-sectional study was conducted on premature infants. Group 1 consisted of all infants diagnosed with ROP (n = 51). The control group included premature infants without ROP. Demographic characteristics and laboratory results were compared between the groups. Data were analyzed using IBM SPSS version 19. Results: The results showed that 34 infants (75.6%) had ROP in both eyes, and the remainder in one eye. Regarding ROP stage, most infants (71.7%) were in stage 2 and zone 3. Hemoglobin, hematocrit, mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC) were significantly lower in the ROP group than in the control group. Furthermore, the comparison of the two groups in terms of anemia (hemoglobin < 11 g/dL) indicated a significantly higher prevalence of maternal anemia in infants with ROP (23 [45.1%]) than in the control group (8 [15.4%]) (P = 0.001). Conclusion: Our results suggest that maternal anemia and hemoglobin level are risk factors for the development of ROP in preterm infants. Given that the diagnosis and treatment of anemia in pregnant women is cost-effective and straightforward, it is crucial to prioritize diagnosis and treatment in mothers at high risk of preterm delivery to potentially reduce the incidence of ROP.